1999
DOI: 10.1212/wnl.52.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Anterior temporal abnormality in temporal lobe epilepsy

Abstract: These frequently seen ipsilateral changes are not caused by gliosis and may reflect a nonspecific increase in water content in the temporal lobe. This may be due to myelin abnormalities or some other as yet unidentified pathologic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
141
0
22

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(179 citation statements)
references
References 21 publications
16
141
0
22
Order By: Relevance
“…These alterations are the most frequent pathological findings presented by these patients 1 . In addition ipsilateral temporal pole signal and volume abnormalities are described as part of the spectrum of MRI features in cases of MTS 2 . The hippocampal sclerosis (HS) is also known as Ammon's horn sclerosis and includes selective hippocampal cell loss, gliosis and synaptic reorganization as the mossy fibers sprouting 3,4 .…”
Section: Flair: Temporal Epilepsy Varella Et Almentioning
confidence: 99%
“…These alterations are the most frequent pathological findings presented by these patients 1 . In addition ipsilateral temporal pole signal and volume abnormalities are described as part of the spectrum of MRI features in cases of MTS 2 . The hippocampal sclerosis (HS) is also known as Ammon's horn sclerosis and includes selective hippocampal cell loss, gliosis and synaptic reorganization as the mossy fibers sprouting 3,4 .…”
Section: Flair: Temporal Epilepsy Varella Et Almentioning
confidence: 99%
“…Emerging work also demonstrates dysregulation of water and K 1 homeostasis in patients with mesial TLE. First, imaging studies demonstrate abnormal T2 prolongation by magnetic resonance imaging in the epileptic hippocampus, possibly partially due to increased water content (Mitchell et al, 1999). This is accompanied by alterations in apparent diffusion coefficient with diffusion-weighted magnetic resonance imaging (Hugg et al, 1999).…”
Section: Human Tissue Studiesmentioning
confidence: 99%
“…Neuroimaging studies revealed that abnormalities in the temporal lobe may coexist with MTS 50,51 . The temporal pole in TLE with MTS patients may present signal abnormalities in up to 75% of the cases 52 .…”
Section: Temporal Lobe Epilepsy: Surgical Pathologymentioning
confidence: 99%
“…Signal abnormalities and atrophy of the temporal pole are ipsilateral to MTS in the majority of patients 53 . Despite the alterations observed in neuroimaging studies, neuropathological studies in patients with such alterations have been inconclusive 51 . Depth EEG studies revealed that the temporal pole cortex may play a pivotal role in originating seizures in TLE patients, with ictal discharges preceding or occurring simultaneously with discharges originated from the ipsilateral hippocampus 50 .…”
Section: Temporal Lobe Epilepsy: Surgical Pathologymentioning
confidence: 99%